Evaluación de una formulación de suela en caucho de acuerdo a la norma NTMD-0099-A5 para Croydon Colombia S.A. (2020)
The purpose of this degree work is to evaluate the development of a new rubber sole formulation based on the requirements of the NTMD-0099-A5 standard of the Ministry of National Defense. For this purpose, 3 main chapters were developed that will be divided into the most important stages of the process, which are: pre-experimentation, experimentation and development of a prototype sole with the final mixture. Finally, in the fifth chapter is the final stage that corresponds to the development of the sole prototype. Having the final combination, the sole is molded into a press, where an existing mold will be taken in the company to be able to take samples from it and re-measure the properties already mentioned. The results are compared between normal and sole-made test specimens, and compliance with NTMD-0099-A5 is checked. To conclude, we find the cost analysis at laboratory scale to determine if the proposal is economically viable.